High-energy ππ scattering without and with photon radiation - Lebiedowicz, Piotr; Nachtmann, Otto; Szczurek, Antoni (Physical review, 2022)
We discuss the processes ππ→ππ and ππ→ππγ from a general quantum field theory (QFT) point of view. In the soft-photon limit where the photon energy ω→0 we study the theorem due to F.E. Low. We confirm his result for the 1/ω term of the ππ→ππγ amplitude but disagree for the ω0 term. We analyze the origin of this discrepancy. Then we calculate the amplitudes for the above reactions in the tensor-Pomeron model. We identify places where “anomalous” soft photons could come from. Three soft-photon approximations (SPAs) are introduced. The corresponding SPA results are compared to those obtained from the full tensor-Pomeron model for c.m. energies √s=10 GeV and 100 GeV. The kinematic regions where the SPAs are a good representation of the full amplitude are determined. Finally we make some remarks on the type of fundamental information one could obtain from high-energy exclusive hadronic reactions without and with soft photon radiation.